Financial Literacy of Shallot Farmers: How Demographic and Socio-Economic Factors Shape Outcomes in Rural Indonesia: Financial Literacy and Farmers (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2024)
Background and purpose - Finances are often an issue for many individuals, including farmers. In 2022, the agricultural sector was the third-largest contributor to the gross domestic product (GDP) at 12.4%, following the industrial sector at 18.3% and the trade sector at 12.9%. In reality, according to BPS data, 14.38 million poor people in Indonesia live in rural areas, most of whom work as farmers. The financial problems of farmers are not only caused by low income but also by low financial literacy. This study aims to determine the level of financial literacy among shallot farmers. Another objective is to analyze the demographic and socio-economic factors that influence the financial literacy of shallot farmers. Methodology - The study was conducted on shallot farmers in Bungur Village, Sukomoro District, Nganjuk Regency. In this study, 111 respondents were selected using purposive sampling technique. The measurement of financial literacy levels used descriptive statistics, and the analysis of the influence of demographic and socio-economic factors on financial literacy used tobit regression analysis. Findings - The results of this study show that the average financial literacy of the respondents was 1.80, which falls into the low financial literacy category. The variables that influence the financial literacy of shallot farmers in Bungur Village are age, education, number of dependents, income, land area, account ownership, and smartphone ownership. Implication - The Financial Services Authority, the Agricultural Extension Agency, and the management of farmer groups collaborate to provide education and training to red onion farmers. These programs should focus on enhancing their financial knowledge and management skills to improve their financial literacy.